2020
DOI: 10.21203/rs.3.rs-35343/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barium enema findings in total colonic aganglionosis: a single-center, retrospective study

Abstract: Background Preoperative diagnosis of total colonic aganglionosis is important for the rational choice of treatment. The present study aimed to evaluate the diagnostic performance of radiographic signs on preoperative barium enema in patients with total colonic aganglionosis. Methods Forty-four patients [41 (3-659) days] with total colonic aganglionosis, including 17 neonatal patients, who received preoperative barium enema at our center, from January 2007 to December 2019 were included. All radiographs were … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
3
0
3
Order By: Relevance
“…Berdon et al reported that the microcolon is seen in less than one‐fourth of patients with total colonic aganglionosis on contrast enema 12 . Although some studies have reported varying frequencies of the microcolon in total colonic aganglionosis, 5,6 a normal caliber colon can also be seen 13 . When the aganglionic segment fails to relax, it may appear as a small‐caliber colon; moreover, it fails to pass meconium, and consequently, the colon may be slightly stretched.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Berdon et al reported that the microcolon is seen in less than one‐fourth of patients with total colonic aganglionosis on contrast enema 12 . Although some studies have reported varying frequencies of the microcolon in total colonic aganglionosis, 5,6 a normal caliber colon can also be seen 13 . When the aganglionic segment fails to relax, it may appear as a small‐caliber colon; moreover, it fails to pass meconium, and consequently, the colon may be slightly stretched.…”
Section: Discussionmentioning
confidence: 99%
“…However, Baad et al reported that contrast enema has moderate specificity and low sensitivity for diagnosing HD in neonates 4 . Furthermore, it is difficult to distinguish total colonic aganglionosis from other low intestinal obstructions using contrast enema 5,6 . Although the use of ultrasound (US) in the diagnosis of HD is limited, a few case studies have described the sonographic findings in fetuses and neonates 7–11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonografi USG transrectal (TRUS) dapat mengevaluasi testis, epididimis, prostat dan vesikula seminalis, dimana pada infeksi TB akan terlihat menebal. USG juga bisa juga untuk melihat lokasi kavitas atau abses di ginjal dan melihat keadaan kandung kemih, serta dapat menilai kondisi organ intra abdomen seperti adanya asites, perlekatan antar ogan, maupun pembesaran organ 1,11,12…”
Section: Gambar 2 Ct Scan Abdomen Dengan Kontras Pada Pasien Dengan T...unclassified
“…2,11 Namun pada studi yang dilakukan oleh Yan, et al (2020), didapatkan bahwa kombinasi gambaran kolon berbentuk tanda tanya disertai refluks katup ileocecal dapat meningkatkan akurasi diagnosis TCA hingga 75%. 12 Diagnosis TCA juga harus dipikirkan jika terdapat gejala klinis obstruksi bertahan tanpa adanya penyebab lain yang diketahui, dengan gambaran radiologis yang menunjukkan gambaran normal kolon. 2,11…”
Section: Kontras Enemaunclassified